Gene expression profiling of recipient immune cells induced by 7 × 19 CAR-T cell dosing in a syngeneic mouse model - Yo Muraki; Yuumi Okuzono; Rina Kurisu; Akiko Abiru; Yukimi Sakoda; Koji Tamada; Chihiro Take (PLoS ONE, 2026)
Chimeric antigen receptor (CAR)-T cell therapy is effective for hematologic malignancies; however, the response of solid tumors is limited because of the immunosuppressive tumor microenvironment, antigen heterogeneity, and lack of persistence of transferred T cells. To overcome these challenges, CAR-T cells expressing interleukin-7 and CC chemokine ligand 19 (7 × 19 CAR-T) were generated to achieve potent antitumor efficacy through the recruitment and proliferation of CAR-T cells and endogenous immune cells. To elucidate the underlying mechanism of 7 × 19 CAR-T cells against solid tumors, we analyzed the cellular composition and gene expression profiles of host immune cells following CAR-T cell infusion in a murine solid tumor model. Antihuman CD20 7 × 19 CAR-T cells were prepared using Thy 1.1 congenic mice and administered to C57BL/6N mice bearing subcutaneous MC38 tumors expressing human CD20. The tumors were harvested 4 days postinfusion to capture early immune responses before overt tumor regression. CD90.1- recipient immune cells were subjected to flow cytometry analysis, and transcriptomic changes were determined using AmpliSeq and single-cell RNA seq. An increase in recipient CD8 + T cells and macrophages was observed in the tumor of mice treated with 7 × 19 CAR-T cells, but not with conventional CAR-T. The expression of chemokines and genes associated with the inflammatory pathway was upregulated only in recipient immune cells of the 7 × 19 CAR-T-treated mice. Single-cell RNA-seq analysis revealed upregulation of pro-inflammatory genes and chemokines in the dendritic cell and monocyte/macrophage populations. These results indicate that 7 × 19 CAR-T cells initiate the early recruitment and activation of host immune cells, which contributes to their superior antitumor activity compared with conventional CAR-T cells.